A circular white-light flare with impulsive and gradual white-light kernels - Q. Hao (Nature Portfolio, 2017)
White-light flares are rare solar events entailing emission in the optical continuum. Here, the authors report a nearly circular white-light flare observed on March 10th 2015 that contains simultaneously both impulsive and gradual white-light kernels.